Amber ale beer enriched with goji berries – The effect on bioactive compound content and sensorial properties. (1st July 2017) - Ducruet, Julien; Rébénaque, Pierrick; Diserens, Serge; Kosińska-Cagnazzo, Agnieszka; Héritier, Isabelle; Andlauer, Wilfried
Graphical abstract: Highlights: Beers with goji berries at the beginning of the process have high sensorial quality. Beers highly evaluated by consumers have also high antioxidant activity content of bioactives. Incorporation of goji berries to brewing process enlarges the range of goji containing foods. Abstract: Goji berries, traditionally used in Chinese medicine, are nowadays gaining popularity in the Western world. Efforts are made to enlarge the offer of goji containing foods. In this study, goji berries were added to ale type beer at different stages of the production process in order to develop a beverage with desirable sensory characteristic and high antioxidant capacity. The obtained beers differed significantly in terms of appearance, taste and antioxidant activity. Consumers preferred beers to which goji berries were added at the beginning of the brewing process. These beers were also characterized by lower turbidity, high color intensity, caramel- and coffee-like taste, high antioxidant activity and high content of bioactives such as rutin and 2-O-β-d -glucopyranosyl-l -ascorbic acid. To conclude, an addition of goji berries to traditional brewing process creates a perspective to enlarge the range of goji containing foods.